Mode of delivery in pregnancies with gastroschisis according to delivery institution. (17th September 2019) - Duncan, Jose; Chotai, Pranit; Slagle, Anna; Talati, Ajay; Huang, Eunice; Schenone, Mauro
Abstract: Purpose: We aim to compare the mode of delivery in pregnancies with gastroschisis delivered in nonacademic institutions with those delivered in an academic center. Material and methods: Chart review from 2008 to 2015 was performed. Cesarean delivery rate (CDR), attempted vaginal delivery rate (AVR), planned cesarean rate (PCR) and adverse neonatal outcomes were compared among pregnancies with gastroschisis delivered in nonacademic hospitals with those delivered in an academic institution. Parametric and nonparametric statistical analysis was performed when appropriate. A multivariable logistic regression mode was utilized to control for confounders. A p value < .05 was considered significant. Results: Mode of delivery was documented in 94 cases (88%). CDR (76.7 versus 41.2%; odds ratios (OR), 4.7; 95%CI, 1.9–11.6) and PCR (55 versus 6.4%; OR 17.9; 95%CI, 4.8–67.4) were higher in those delivered in nonacademic centers. AVR was lower in the nonacademic group (45 versus 93.6%; OR 0.02; 95%CI, 0.01–0.2). Neonatal intensive care length of stay (56 days [IQR, 34–102 days] versus 36 days [IQR, 26–60 days; p  = .018]) was longer in the nonacademic group. Other neonatal adverse outcomes studied were not statistically different between groups. Conclusions: In our population, delivery at nonacademic institutions in pregnancies with gastroschisis may be associated with higher cesarean delivery rates. These findings may add information for the delivery planning of pregnancies complicated by this condition. Rationale: In our study we aim to compare the mode of delivery in pregnancies with gastroschisis delivered in nonacademic institutions with those delivered in an academic center. Our results suggest, that delivery at nonacademic institutions in pregnancies with gastroschisis may be associated with higher cesarean delivery rates. These findings may add information for the delivery planning of pregnancies complicated by this condition.